Effectiveness of a video lesson for the correct use in an emergency of the automated external defibrillator (AED) - Rubbi, Ivan; Lapucci, Giorgio; Bondi, Barbara; Monti, Alice; Cortini, Carla; Cremonini, Valeria; Nanni, Eleonora; Pasquinelli, Gianandrea; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Every year around 275 thousand people in Europe and 420 thousand in the United States are affected by sudden cardiac arrest. Early electrical defibrillation before the arrival of emergency services can improve survival. Training the population to use the AED is essential. The training method currently in use is the BLSD course, which limits training to a population cohort and may not be enough to meet the requirements of the proposed Law no. 1839/2019. This study aims to verify the effectiveness of an online course that illustrates the practical use of the AED to a population of laypeople. Methods: An observational study was conducted to compare a lay population undergoing the view of a video spot and a cohort of people who had participated in BLSD Category A courses. The performances of the two groups were measured immediately after the course and 6 months later. Results: Overall, the video lesson reported positive results. Six months later the skills were partially retained. The cohort that followed the video lesson showed significant deterioration in the ability to correctly position the pads and in safety. Conclusions: Although improved through significant reinforcements, the video spot represents a valid alternative training method for spreading defibrillation with public access and could facilitate the culture of defibrillation as required by the new Italian law proposal.